DEVELOPING PRACTICAL GUIDELINES OF TEACHING WRITING USING COOPERATIVE INTEGRATED READING AND COMPOSITION - Ashri Shollina; Dewi Rochsantiningsih; Joko Nurkamto (SALEE: Study of Applied Linguistics and English Education, 2020)
Cooperative integrated reading and composition (CIRC) technique gives the opportunities for the students to increase language skills, especially applicability of reading activities and composition writing techniques. The absence of a guideline of teaching writing using certain technique results a less effective process of teaching writing. Thus, this research and development study was aimed to investigate the quality of the existing guidelines of writing in junior high school and the development of the practical guidelines of teaching writing in SMPN of Karanganyar Central Java using Cooperative Integrated Reading and Composition. This research was conducted through two stages; exploration stage and product development stage. The finding of the exploration stage was obtained through several techniques like interview, observation, document analysis and questionnaire distribution which revealed that there was no certain writing guideline used to teach. The teachers used textbook, syllabus and lesson plan as the guidance of teaching writing. Thus, the writing guideline should be developed by considering the need of the teacher and the students. The guideline prototype was developed by considering some aspects. It contained theoretical theories of writing, CIRC and teaching writing to Junior High School and the implementation of teaching writing of descriptive, recount, and narrative texts. Then, it had been validated by the expert and tried out thrice in one class of eighth graders of SMPN in Karanganyar Central Java. Through focus group discussion, the guideline prototype was changed and revised to be the final draft of writing guideline. Therefore, through the stages, it could be concluded that the practical guideline was feasible to be used by the teachers to teach writing to junior high school students.